2019
DOI: 10.1111/pai.13140
|View full text |Cite
|
Sign up to set email alerts
|

The severity of reaction after food challenges depends on the indication: A prospective multicenter study

Abstract: Background: There are expanding indications for oral food challenges (OFCs).Although several studies have examined the risk of OFCs, little has been reported on allergic reactions during OFCs depending on the indication. This study assessed the prevalence, severity, and treatment of allergic reactions depending on the indication for OFCs. Methods:We performed a prospective multicenter study between March 2012 and May 2013. Severity of symptoms elicited by OFCs was classified according to grading of anaphylaxis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
2
1

Year Published

2020
2020
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(20 citation statements)
references
References 25 publications
0
17
2
1
Order By: Relevance
“…However, OFC is the gold standard, particularly when it comes to eliminating the risk of unnecessary food avoidance. 12,16 Our OFC numbers are either slightly high 17,18 or slightly low 19,20 compared with previous studies. The numbers of OFCs are closely related to infrastructure and experience.…”
Section: Ofcs and Outcomescontrasting
confidence: 60%
“…However, OFC is the gold standard, particularly when it comes to eliminating the risk of unnecessary food avoidance. 12,16 Our OFC numbers are either slightly high 17,18 or slightly low 19,20 compared with previous studies. The numbers of OFCs are closely related to infrastructure and experience.…”
Section: Ofcs and Outcomescontrasting
confidence: 60%
“…12 Egg followed the same trend, causing an adverse reaction in 19.8% OFCs (n = 49). The Japanese study conducted by Itazawa et al 4 actually found egg at the first place of challenged foods.…”
Section: Discussionmentioning
confidence: 97%
“…A similar condition was found in Perry et al's study 2 : severe reactions occurred in 28% of the OFCs, but epinephrine administration was administered in 11%. Moreover, a Japanese multicentric study 4 found 2258 positive OFCs, of which 991 (43.9%) were classified as grade 1, 736 (32.6%) were classified as grade 2, 340 (15.1%) were classified as grade 3, and 191 (8.5%) were classified as grade 4-5. Epinephrine was administered only in 7.1% (n = 160) of positive OFCs (44.5% of patients with grade 4-5 of anaphylaxis).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A recent prospective study of 5062 pediatric OFCs revealed that the prevalence, severity, and treatment of allergic reactions depended on the indication with the most severe reactions occurring when the indication was to discover the threshold to start oral immunotherapy. 12 In 74 patients with food allergy confirmed for a clinical trial, 39% were treated with epinephrine. 13 Therefore, the highest severity of OFC reactions tend to occur in the patients who are also at the highest probability of being allergic.…”
Section: Severity Of An Allergic Reactionmentioning
confidence: 99%